Allelic structures and mechanisms of copy number change at the human DEFA1A3 copy number variable locus - Black, Holly Ann (2014)
The DEFA1A3 locus on human chromosome 8p23.1 exhibits extensive copy number variation; individuals have between 3-16 copies of DEFA1A3. The region has additional complexity in that each repeat unit contains a gene locus that can be occupied by one of two different genes, DEFA1 or DEFA3. These encode the human neutrophil peptides (HNPs) 1-3, antimicrobial peptides involved in the innate immune response. In order to understand the mutational processes and evolutionary history of a complex locus like DEFA1A3, spatial information is essential. Whilst haplotype DEFA1A3 copy numbers and haplotype ratios of DEFA1 vs. DEFA3 have been determined, little is known about the features shared by, and the structures of, related haplotypes.